Effect of creatine supplementation on intermittent sprint running performance in highly trained athletes - Delecluse, C.; Diels, R.; Goris, M. (The Journal of Strength and Conditioning Research, 2003)
This study examined the impact of short-term (7-day), high-dose (0.35 g·kg1·d1) oral creatine monohydrate supplementation (CrS) on single sprint running performance (40 m, <6 seconds) and on intermittent sprint performance in highly trained sprinters. Nine subjects completed the double-blind cross-over design with 2 supplementation periods (placebo and creatine) and a 7-week wash-out period. A test protocol consisting of 40-m sprint runs was performed, and running velocity was continuously recorded over the total distance. The maximal sprint performance, the relative degree of fatigue at the end of intermittent sprint exercise (6 × 40 m, 30-second rest interval), as well as the degree of recovery (120-second passive rest) remained unchanged following CrS. There were no significant changes related to CrS in absolute running velocity at any distance between start and finish (40 m). It was concluded that no ergogenic effect on single or repeated 40-m sprint times with varying rest periods was observed in highly trained athletes.